Pengaruh Program Undian Berhadiah Umrah dan Citra Merek terhadap Minat Beli di Assalam Hypermarket Kartasura - Ardi Wahyu Tri Aryanto; Muhammad Raqib (UIN Raden Mas Said Surakarta, 2020)
This study aims to analyze the effect of the Umrah prize lottery program and brand image toward buying interest in Assalaam Hypermarket Kartasura. The dependent variable in this study is buying interest. Meanwhile, the independent variables are the Umrah prize lottery and brand image. The population in this study included the entire population of the Kartasura sub-district as many as 109,549. The sample was selected by using the accidental sampling method and the Slovin formula with an error rate of 10% and obtained 100 respondents. This study was a quantitative study using multiple linear regression as an analysis technique. The results show that the Umrah prize lottery affects buying interest. Furthermore, brand image affects buying interest. And finally, the Umrah prizeÂ lotteryÂ and brand image affect buying interest.